Perumusan Product Vision Sistem Informasi Desa Berbasis Goal-Oriented Requirements Engineering untuk Mendukung Transformasi Digital - Alkiano Fridho Aji Mahadiva; Wahyu Kusuma (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2026)
Village digitalization faces various challenges, such as low digital literacy, limited infrastructure, and lack of community participation. Problem identification in Bomo Village shows 90% of respondents complain about manual administrative services, 80% face difficulties accessing village information, and 75% desire digital participation media, indicating that the village information system has not fully addressed the needs of the village community. This study aims to formulate a product vision for a village information system using the Goal-Oriented Requirements Engineering (GORE) approach to create a more structured, participatory system aligned with village strategic objectives. The methodology includes semi-structured interviews, field observations, and questionnaires distributed to villagers and village officials. Data were analyzed using Goal Tree Model (GTM) and Goal-oriented Requirement Language (GRL) to map stakeholder goal hierarchies. The results yielded four strategic goals: improving public service efficiency, empowering the local economy, promoting village potential, and enhancing community participation through digital media. This research produces a product vision framework that can be adopted by other villages for developing information systems adaptive to local community needs, while supporting inclusive and sustainable implementation of village digitalization.